Tumor Necrosis Factor-α Promotes the Tumorigenesis, Lymphangiogenesis, and Lymphatic Metastasis in Cervical Cancer via Activating VEGFC-Mediated AKT and ERK Pathways - Xiao Chen; Luping Lin; Qiaoling Wu; Sang Li; Huihui Wang; Yang Sun (Mediators of Inflammation)
Background. Lymphatic metastasis is a common phenomenon of cervical cancer. Tumor necrosis factor-α (TNF-α) was found to be closely associated with lymphatic cancer metastasis. However, the mechanism through which TNF-α regulates lymphatic metastasis in cervical cancer remains unclear. Methods. In this study, cervical cancer cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) with or without TNF-α for 48 h, and then the corresponding conditional medium (CM-TNF-α or CM) was collected. The level of vascular endothelial growth factor (VEGFC) in the corresponding CM was then detected using an enzyme-linked immunosorbent assay (ELISA). Next, human lymphatic endothelial cells (HLECs) were cultured in CM-TNF-α or CM for 48 h. Cell viability was measured using the cell counting kit-8 (CCK-8) assay, and angiogenesis was detected using a tube formation assay. Subsequently, the expressions of AKT, p-AKT, ERK, and p-ERK in HLECs were detected using western blotting. In addition, to further investigate the effect of TNF-α on the progression of cervical cancer, a C33A subcutaneous xenograft model was established in vivo. Results. We found that TNF-α significantly stimulated cervical cancer cells to secrete VEGFC. Additionally, the CM collected from the TNF-α-treated cervical cancer cells notably promoted the proliferation, migration, and angiogenesis of HLECs; however, these changes were reversed by MAZ51, a VEGFR3 inhibitor. Moreover, TNF-α obviously elevated D2-40 and VEGFC protein expressions in tumor tissues, promoting lymphangiogenesis and lymphatic metastasis in vivo. Meanwhile, TNF-α markedly upregulated p-AKT and p-ERK expressions in tumor tissues, whereas these changes were reversed by MAZ51. Conclusion. Collectively, TNF-α could promote tumorigenesis, lymphangiogenesis, and lymphatic metastasis in vitro and in vivo in cervical cancer via activating VEGFC-mediated AKT and ERK pathways. These results may provide new directions for the treatment of cervical cancer.